The unfaithful Irish voter. Issue 3 (3rd July 2019) - Marsh, Michael
ABSTRACT: Local and European elections have been held simultaneously since 1999. These offer an interesting context to look at the importance of party, both across each pair of elections and across these elections and future voting intentions. Analysis of behaviour in these elections suggests the influence of party is far from dominant. Exit polls and the 2002-7 Irish National election Study show around half of all voters supporting different parties in the two elections, and in some cases expressing vote intentions for the next general election that is different again. The elections of 2019 mark a low point in such cohesion.